Studies on as separation behaviour of polymer blending PI/PES hybrid mixed membrane: Effect of polymer concentration and zeolite loading - Ahmad Fauzi Ismail; Tutuk Djoko Kusworo (Chemical Engineering Diponegoro University, 2014)
This study is performed primarily to investigate the effect of polymer concentration of polyimide/polyethersulfone (PI/PES) blending on the gas separation performance of hybrid mixed matrix membrane. In this study, PI/ (PES)–zeolite 4A mixed matrix membranes were casted using dry/wet phase inversion technique. The efefct of PI/PES concentrations and zeolite loading on the dope solution were investigated for gas separation performance. The results from the Field Emission Scanning Electron Microscopy (FESEM) analysis confirmed that polymer concentration and zeolite loading was affected the morphology of membrane and gas separation performance. ‘Sieve-in-a-cage’ morphology observed the poor adhesion between polymer and zeolite at higher zeolite loading. The gas separation performance of the mixed matrix membranes were relatively higher compared to that of the neat polymeric membrane.